The magnetic behaviors and magnetocaloric effect of a nano-graphene bilayer: A Monte Carlo study - Sun, Lei; Wang, Wei; Liu, Cong; Xu, Bing-hui; Lv, Dan; Gao, Zhong-yue (Superlattices and microstructures, 2021)
By means of the Monte Carlo simulation, the influence of exchange couplings and the applied magnetic field on the magnetic behaviors and magnetocaloric effect of a ferromagnetic mixed-spin (3/2, 5/2) nano-graphene bilayer have been investigated. It is found that the magnetic behaviors can be enhanced by increasing the exchange couplings and the applied magnetic field. The internal energy decreases with increasing two physical parameters mentioned above. In addition, the maximums of the magnetic entropy change and adiabatic temperature change would appear near the critical temperature, the values of them increase with decreasing exchange couplings or increasing the applied magnetic field. The maximum of the -ΔSm can be found to be 0.293 for h = 3. Besides, the relative cooling power can be enhanced as the exchange couplings decrease or the applied magnetic field increases. •The ferromagnetic mixed-spin (5/2, 3/2) nano-graphene bilayer has been investigated by Monte Carlo simulation.•Magnetic properties can be enhanced by increasing the exchange couplings and the applied magnetic field.•Magnetic entropy change and adiabatic temperature change increase with exchange couplings decreasing.•Magnetic entropy change and adiabatic temperature change increase with the applied magnetic field increasing.•The relative cooling power enhanced as exchange couplings decreases or the applied magnetic field increases.